International Monetary Fund Annual Report 2008 : Making the Global Economy Work for All. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The Annual Report 2008 to the Board of Governors reviews the IMF's activities and policies during the financial year (May 1, 2007, through April 30, 2008). There are five chapters: (1) Overview: Refocusing the IMF; (2) Developments in the Global Economy and Financial Markets; (3) Fostering Macroeconomic and Financial Stability and Growth Through Surveillance; (4) Program Support and Capacity Building; and (5) Governance, Organization, and Finances. The full financial statements for the year, other appendixes, and materials supplementing the text are provided on a CD-ROM.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet